NUTRIENT CONTENT OF BIOENZYME AND ITS EFFECT ON GROWTH AND PHYTOCHEMICAL COMPOSTION OF PLECTRANTHUS AMBOINICUS - P. AISHWARYA; S . VIJAYALATHA (The Bioscan, 2023)
A substitute for chemical fertilizers is the need of the hour. The objective of this study was to assess if bioenzymes which have been extensively studied for its potential as a cleaning agent, could be used as a biofertilizer. Bioenzyme was prepared using jaggery, Citrus limetta peel, and water in ratio 1:3:10 respectively with Saccharomyces cerevisiae. This study involved analysis of nutritive content of bio enzyme and effects of its use on growth parameters (shoot length, number of leaves) and phytochemical composition of leaves (Chlorophyll and flavonoids) of Plectranthus amboinicus. The results indicated that primary nutrients such as Nitrogen (300mg/L), Potassium(379mg/L), Phosphorous(69mg/L) and secondary nutrients such as Iron (1.33 mg/L), Copper (6.99mg/ L) and Calcium(288mg/L) were in adequate amounts in the bioenzyme. Control and test groups with three saplings each were used to assess the potential of bioenzyme as fertilizer. The test group plants were grown in soil supplemented with bioenzyme and were also irrigated with diluted bioenzyme. Significant increase was observed in shoot length, number of leaves (p<0.05) and flavonoid content of leaves (p<0.01) in the test group compared to the control group. No statistically significant difference was observed in chlorophyll content.